Application Of Traditional Javanese Ornaments In Historic Buildings: A Case Study of Ndalem Kalitan In Surakarta - Salim; Amin Sulistiyowati; Heriyanto Atmojo (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2026)
Ndalem Kalitan in Surakarta is a historic building rich in cultural and historical value, reflected in the carved ornaments that adorn the doors, windows, pillars, and interior elements. This study aims to identify the form, meaning, and historical value of the ornaments and carvings on Ndalem Kalitan and analyze their potential as a source for historical learning. The study employed a qualitative descriptive method, collecting data through observation, documentation, and interviews with informants familiar with the history of Ndalem Kalitan and traditional Javanese carving. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the carvings on Ndalem Kalitan contain historical values ​​related to the Javanese philosophy of life, symbols of social status, and the influence of cultural acculturation. These values ​​are relevant as a learning resource, particularly for local ornaments, to foster awareness and appreciation for regional cultural heritage.